Co-Existence Of Pemphigus Foliaceous And Squamous Cell Carcinoma Of Oesophagus - Rani mittal Radha; Chopra Adarsh; Gupta Seema (Wolters Kluwer Medknow Publications, 1998)
One 50 year old female had recurrent vesiculobullous lesions and progressive dysphagia since 3 months. Both complaints started almost simultaneously, although she had dyspepsia and indigestion since 1 year. Histopathology confirmed that she had pemphigus foliaceous ano associated squamous cell carcinoma of oesophagus. The co-existence of pemphigus and malignancy is unusual. The two conditions may be causally related as pemphigus antibodies may lead to production or release of squamous cell carcinoma related antigens. Present case is being reported because of its rare association